Rococo fiction in France, 1600-1715 : seditious frivolity - Stedman, Allison, 1974- (Transits (Bucknell University), 2012)
Rococo Fiction in France, 1600-1715: Seditious Frivolity by Allison Stedman, PhD makes a case for the rococo as a seventeenth-century literary phenomenon that provided an aesthetic and ideological counterpoint to the emergence of the classical-baroque style and the rise of French political absolutism. Tracing the rococo's evolution over the course the seventeenth-century, and exploring its radicalization during the 1670s, 80s and 90s, the study unearths the rococo's counter-vision for the origins and trajectory of the French Enlightenment.